Guidelines for Developing Tourism Market Potentials and Package Tour of Sukhothai Old Town Community as the World Creative City in the New Normal Way of Living - Sritong, Chaloempon; Teangsompong, Teerapong; Likitsarun, Nuchpravee (Community and Social Development Journal, 2021)
This article aimed to study 1) the community contexts, 2) the market potentials and the guidelines for developing marketing potentials, and 3) the package tour of Sukhothai Old Town Community as the World Creative City of Thailand in the New Normal way of living. This qualitative approach used an in-depth interview, informal interview, and participant observation from 27 key informants (i.e., community leaders, government representatives, and tourism entrepreneurs in Sukhothai province) chosen by purposive and snowball sampling. All data were analyzed using content analysis. The findings showed that 1) the Sukhothai Old Town Community was established surrounding the Sukhothai Historical Park. The community comprises 12 smaller communities, all of which generate tourism products linking to the major tourist attractions. 2) The community has outstanding tourism products because of its long-standing cultural heritage, for example, chinaware, Khao Tok Pra Ruang (literally “popped rice of Phra Ruang”), Lao Puan Traditional Clothing, and the Bai Si ceremony (The ceremony of welcome). Besides, the community has developed the guidelines for tourism, for example, the package tour based on tourist’s behaviours and individual interests, the creation of identity products for Sukhothai Old Town, the upgrading of the Safety and Health Administration (SHA) in the New Normal way of living among community tourism entrepreneurs. 3) The development of a 3-day and 2-night package tour of Yon Moradok Phra Ruang (literally “The appreciation of Moradok Phra Ruang”) is initiated by the community in collaboration with the Thai Federation of Provincial Tourist Association for tourism market promotion.